A CAD of fully automated colonic polyp detection for contrasted and non-contrasted CT scans - Tulum, Gokalp; Bolat, Bulent; Osman, Onur (SPRINGER HEIDELBERG, 2017)
Computer-aided detection (CAD) systems are developed to help radiologists detect colonic polyps over CT scans. It is possible to reduce the detection time and increase the detection accuracy rates by using CAD systems. In this paper, we aimed to develop a fully integrated CAD system for automated detection of polyps that yields a high polyp detection rate with a reasonable number of false positives. The proposed CAD system is a multistage implementation whose main components are: automatic colon segmentation, candidate detection, feature extraction and classification. The first element of the algorithm includes a discrete segmentation for both air and fluid regions. Colon-air regions were determined based on adaptive thresholding, and the volume/length measure was used to detect air regions. To extract the colon-fluid regions, a rule-based connectivity test was used to detect the regions belong to the colon. Potential polyp candidates were detected based on the 3D Laplacian of Gaussian filter. The geometrical features were used to reduce false-positive detections. A 2D projection image was generated to extract discriminative features as the inputs of an artificial neural network classifier. Our CAD system performs at 100% sensitivity for polyps larger than 9 mm, 95.83% sensitivity for polyps 6-10 mm and 85.71% sensitivity for polyps smaller than 6 mm with 5.3 false positives per dataset. Also, clinically relevant polyps (6 mm) were identified with 96.67% sensitivity at 1.12 FP/dataset. To the best of our knowledge, the novel polyp candidate detection system which determines polyp candidates with LoG filters is one of the main contributions. We also propose a new 2D projection image calculation scheme to determine the distinctive features. We believe that our CAD system is highly effective for assisting radiologist interpreting CT.
Keywords: Polyp detection; Computer-aided detection; Colon segmentation; Computed tomography images; FALSE POSITIVES; COLONOGRAPHY; REDUCTION; CLASSIFICATION; SEGMENTATION; DIAGNOSIS; SCHEME; Engineering; Radiology, Nuclear Medicine & Medical Imaging; Surgery